I am reading P. Li's lectures on Geometric analysis. On page 14, the author defines the second covariant derivative as follows:

Let $f$ be a smooth function on $M$. $\omega_1, \cdots, \omega_n$ be a local orthonormal basis of $T^*M$ around a fixed point $p$. And $d\omega_i=\sum_j\omega_{ij}\wedge\omega_j$. Then $$df=\sum_i f_i\omega_i$$ THen the author give the definition: $$ f_{ij}\omega_j=df_i+f_j\omega_{ji}. $$

My question is how to understand this definition compare with the usual one, i.e. $$ \nabla^2_{X,Y}f=XY(f)-\nabla_XY (f) $$

Also the third order covaiant derivative defines in the similar manner: $$ f_{ijk}\omega_k=df_{ij}+f_{kj}\omega_{ki}+f_{ik}\omega_{kj} $$ The similar question for this expression, how to understand these indices?

Thank you for any detailed answer, I am kind of afraid of this local calculations compare with the ususal global definition. However, in most papers, the local calculations are more common. So I want to figure it out clearly.


They are actually the same. I am used to a slightly different notations and I will stick to mine. Let $\{\omega^i\}_{i=1}^n$ be a local orthonormal coframe dual to the orthonormal frame $\lbrace e_i\rbrace_{i=1}^n$ and we define the connection $1$-form $\omega_i^j$ by $\nabla _X e_i = \omega_i^j(X)e_j$ (Einstein notation). Then by differentiating $\delta_i^j=\omega^j(e_i)$, we have $\nabla _X \omega^j =-\omega_i^j (X)\omega^i$.

The equation $d\omega^i=\omega^j\wedge \omega_j^i$ (note that $\omega_i^j$ is $\omega_{ij}$ in Peter Li's note, and also $\omega_i^j=-\omega_j^i$ due to orthogonality), known as the (first) Cartan's structure equation, can be obtained by $$d\omega^i(X, Y)= (\nabla _X \omega^i)(Y)- (\nabla _Y \omega^i)(X)=-\omega^i_j(X)\omega^j(Y)+\omega^i_j(Y)\omega^j(X)=(\omega^j\wedge \omega ^i_j)(X, Y).$$ Alternatively, from the above it's easy to see that if $\omega^i_j $ satisfies the Cartan's equation, then $\nabla _X \omega^j =-\omega_i^j (X)\omega^i$. The connection 1-forms are exactly the analogue of the Christoffel symbols in a coordinates system.

Recall that for a function $f$, the covariant derivative $\nabla f$ coincides with $df$, i.e. $\nabla f(X)= df(X)(=X(f))$. The second covariant derivative (i.e. Hessian) is given by $\nabla ^2 f :=\nabla (\nabla f)= \nabla (df)$. In an orthonormal frame, we have \begin{equation*} \begin{split} f_{ij}:=(\nabla ^2 f)(e_i , e_j)= (\nabla (\nabla f))(e_i, e_j):= (\nabla _{e_i}\nabla f)(e_j)= &\nabla _{e_i}(\nabla _{e_j}f)- (\nabla f)(\nabla _{e_i}e_j)\\ =& e_i(e_j(f))-(\nabla _{e_i}e_j)f\\ =& e_i(f_j)-(\nabla _{e_i}e_j)f. \end{split} \end{equation*} where $f_j:= e_j(f)$. Using the language of moving frames, this computation becomes \begin{equation*} \begin{split} f_{ij}= e_i(f_j)-f_k \omega_j^k(e_i). \end{split} \end{equation*} As $dh=e_i (h) \omega^i$ for a function $h$, this means that $$ f_{ij}\omega^i= df_j- f_k \omega^k_j= df_ j + f_k \omega_k^j.$$

It turns out that it doesn't matter if we define $f_{ij}$ as $\nabla ^2 f(e_i, e_j)$ or $\nabla ^2 f (e_j, e_i)$. However, for the third derivative, the order of $i, j, k$ does matter. In Peter Li's note, $f_{ijk}$ is defined as $(\nabla _k (\nabla ^2 f))(e_j, e_i)$, which in my convention is $(\nabla (\nabla ^2 f))(e_k, e_j, e_i)= :\nabla ^3 f(e_k , e_j, e_i)$. With this in mind, we now compute $f_{ijk}$.

As $\nabla ^2 f= f_{lm}\omega^l \omega^m$, we have \begin{equation*} \begin{split} f_{ijk}= (\nabla _k (\nabla ^2f))(e_j, e_i) =& \nabla _k (\nabla ^2 f (e_j , e_i))- \nabla ^2 f (\nabla _k e_j , e_i)-\nabla ^2 f ( e_j, \nabla _k e_i)\\ =&e_k(f_{ij})- \omega_j^l(e_k)f_{li}-\omega_i^l (e_k)f_{jl}\\ =& (df_{ij}- f_{li}\omega^l_k- f_{jl}\omega^l_i)(e_k) \end{split} \end{equation*} Therefore $$ f_{ijk}\omega^k=df_{ij}- f_{li}\omega^l_k- f_{jl}\omega^l_i=df_{ij}+f_{li}\omega^k_l+f_{jl}\omega^i_l.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.